Testing the Triple‐Match Principle in the Technology Sector: A Two‐Wave Longitudinal Panel Study. Issue 2 (22nd August 2012) - Van de Ven, Bart; de, Jan; Vlerick, Peter
<x xml:space="preserve">Abstract</x> The present study investigates the issue of match between job demands and job resources in the prediction of changes in job‐related well‐being outcomes as outlined by the Demand‐Induced Strain Compensation (DISC) model. Job demands, resources, and well‐being outcomes are considered to be multidimensional constructs comprising physical, cognitive, and/or emotional components. The Triple‐Match Principle (TMP) proposes that the strongest, interactive relationships between job demands and resources are observed when demands, resources, and outcomes are based on identical dimensions. This principle was tested using a two‐wave longitudinal panel study among 720 Belgian employees in the technology sector. Analyses were conducted with cross‐lagged structural equation modeling, and results tend to confirm the matching hypothesis. Specifically, the likelihood of finding valid interaction effects was nearly linearly related to the degree of match between demands, resources, and outcomes. Generalisability of the TMP in the technology sector was shown. Practically, findings indicate that enhancing specific, matching, job resources enables employees to deal with corresponding high job demands to improve employee well‐being.